The Importance of Pediatrics in Feeding Children with Minerals - Akbarova Rano Mirzarabovna (Genius Journals, 2023)
Correction of multivitamin deficiency should be aimed not only at additional intake of missing substances, but also at improving their absorption, as well as the synthesis of vitamins in the body. The bulk of vitamin-mineral complexes (VMC) contain recommended doses of the most essential vitamins and microelements. But not all components of VMC can be fully absorbed, since quite often patients with multivitamin deficiency also have problems with the intestinal microbiota, which reduces the availability of the ingredients contained in VMC. This article is devoted to the feasibility of additional intake of vitamins, their role in the body and manifestations of deficiency.
Keywords: Children; vitamins; prevention; macroelements